TIP1;1 expression could modulate the recovery of stomatal opening during rehydration in Sorghum bicolor - Schley, Thayssa Rabelo [UNESP]; Franco, Danilo Miralha [UNESP]; Araújo Junior, João Pessoa [UNESP]; de Godoy Maia, Ivan [UNESP]; Habermann, Gustavo [UNESP]; de Almeida, Luiz Fernando Rolim [UNESP] (Elsevier, 2022)
Stomatal conductance (gs) takes longer to recover after drought when compared to leaf water potential or leaf water content (RWC). Aquaporins, known for transporting water through membranes, could modulate gs recovery. Using Sorghum bicolor, we tested whether members of the plasma membrane (PIP) and tonoplast (TIP) intrinsic aquaporin subfamilies could influence gs after a 20-day drought. Potted plants under soil field capacity (control), severe water deficit (SWD; 30% (m/m) soil water content), and progressive severe water deficit (PSWD; water withheld until maximum stress) were used. Soil (Ψsoil), predawn (ΨPD), and midday (ΨMD) leaf water potentials, photochemical, and gas exchange parameters were measured during drought and 12 days of recovery. After 17 days of drought, gs of SWD and PSWD was 4-times lower than control, and it took 6 days to recover. ΨPD, ΨMD, and RWC, however, recovered after 24 h. SbPIP1;2, SbPIP2;5, and SbTIP1;1 were all down-regulated on the day of maximum stress, but only SbTIP1;1 showed consistent alleviation of its down-regulation as gs recovered. SbTIP1;1 expression was positively correlated with gs, leaf transpiration, and hydraulic conductivity (KL), but only in SWD plants. The slow gs recovery seems to be associated with the alleviation of SbTIP1;1 down-regulation as rehydration progresses.
Keywords: Aquaporins; Drought recovery; gs; PIP; Reirrigation; TIP